Hemodynamic Changes after Continuing or Omitting Regular Angiotensin Converting Enzyme Inhibitors before Cataract Surgery: A Comparative Study - Khademi, Saeed; Jouybar, Reza; Ahmadi, Sedigheh; Asmarian, Naeimehossadat; Ghadimi, Maryam; Salari, Mehrdad; Emami, Soodabeh (Current Hypertension Reviews, 2023)
Aims: In this study, we aimed to appraise the effects of interrupting (discontinuing) vs. continuing Angiotensin receptor blockers (ARBs) and Angiotensin-Converting Enzyme Inhibitors (ACEIs) on the hemodynamic changes of patients during and after cataract surgery. Methods and Materials: Patients aged 40-70 years, American society of anesthesiologist (ASA) class II, taking ACEI/ARB medications, who were admitted to Khalili hospital (Shiraz, South of Iran) for cataract surgery, were enrolled in the study. Patients were randomly divided into two groups for continuing or withdrawing the use of ACEI/ARBs. Group 1 included the patients who continued ACEI/ARB administration, and group 2 included those who discontinued them before surgery. In the operating room, relevant demographic information was collected in addition to the data on patients’ basic clinical status, including heart rate and blood pressure, before induction of anesthesia, during, and after that. The collected data were analyzed using SPSS 21, and p-values < 0.05 were considered statistically significant. Results: Any significant differences were not revealed in demographic variables (age, sex, diabetes, hypertension, Myocardial infarction, Smoking, and duration of drug therapy) between the two groups. Time effect was significant (p<0.001) for systolic blood pressure, diastolic blood pressure, and heart rate, and interaction between time*group was not significant (p = 0.431, p = 0.566, and p = 0.355) for systolic blood pressure, diastolic blood pressure, and heart rate. However, the group effect wasn’t significant (p=0.701, p=0.663, and p=0.669) for systolic blood pressure, diastolic blood pressure, and heart rate. Conclusion: It seems that in some minor surgeries, such as cataract surgery, withdrawal or continuation of ACEIs/ARBs have no significant effect on the hypotension and heart rate of patients during orafter an operation.
Keywords: angiotensin-converting enzyme inhibitors